2018
DOI: 10.1021/acsphotonics.8b01049
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance 2D MoS2 Phototransistor for Photo Logic Gate and Image Sensor

Abstract: Two-dimensional (2D) MoS2 is a representative n-type transition-metal dichalcogenide (TMD) semiconductor that has great potential for future nanoscale electronic and optoelectronic applications. Here, we report a high-performance MoS2 phototransistor that exhibits a photoresponse in the 400–700 nm range with the maximum responsivity of over 1 × 104 A/W. As a more sophisticated optoelectronic application than a simple unit device, it is implemented in a photoinverter (NOT logic gate) connected to an external re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…To obtain the colored image, each pixel of the image sensor array was measured with the turtle stencil under RGB light that differs from pixel to pixel, respectively. The light stencil projection method was inspired and developed from previous reports 30 , 64 . Lee et al 30 reported a single-pixel imager and the image scanning system with three different light sources (RGB).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the colored image, each pixel of the image sensor array was measured with the turtle stencil under RGB light that differs from pixel to pixel, respectively. The light stencil projection method was inspired and developed from previous reports 30 , 64 . Lee et al 30 reported a single-pixel imager and the image scanning system with three different light sources (RGB).…”
Section: Methodsmentioning
confidence: 99%
“…227 The phototransistor fabricated from multilayer MoS 2 using graphene source/drain electrodes showed a high photoresponsivity of 1 Â 10 4 A W À1 in the wavelength range of 470-600 nm. 228 Chen et al 229 developed n-n-type vdWHs using multilayer MoS 2 coated with a layer of nitrogen-doped graphene QDs (N-GQDs) to complement each other with their strong characteristics to improve the carrier mobility. In this hybrid structure, 230 by adding hydrogen gas during the CVD growth process, which resulted in centimeter-long monolayer MoS 2 continuous lms on graphene.…”
Section: Mos 2 /Graphene Hybrid Heterostructures For Exible Photodetmentioning
confidence: 99%
“…High photoresponsivities ranging from 10 3 A W À1 to 10 10 A W À1 have been observed for the graphene/MoS 2 hybrid structurebased photodetectors. 126,[226][227][228] Han et al 300 developed photodetectors using CVD-grown MoS 2 monolayers with both Au and graphene electrodes. MoS 2 photodetectors with graphene electrodes showed the current I on /I off ratio of 1 Â 10 5 and mobility of 0.48 cm 2 V À1 s À1 compared to 2 Â 10 3 and 0.1 cm 2 V À1 s À1 with gold electrodes.…”
Section: Graphene Electrodesmentioning
confidence: 99%
“…One possible reason of this sublinear relationship between responsivity and light power is the reduction in the number of photogenerated carriers due to exciton recombination at high charge carrier density . Under weak light intensity of 3.5 µW cm −2 , the 2F‐4‐TFPTA 2D phototransistor exhibited responsivity of 3.6 × 10 3 A W −1 at the accumulation region, which is higher than that of a single‐crystal silicon phototransistor (≈3 × 10 2 A W −1 ) and comparable to that of conventional MoS 2 2D phototransistors (≈10 3 A W −1 ) . As expected from the absorption characteristics, the 2F‐4‐TFPTA 2D phototransistor is much more sensitive to green light than blue and red light.…”
mentioning
confidence: 93%